The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1677/joe.0.1650669
|View full text |Cite
|
Sign up to set email alerts
|

Radioimmunoassay of plasma ouabain in healthy and pregnant individuals

Abstract: Ouabain was recently isolated from human plasma, bovine hypothalamus and bovine adrenal in attempts to identify endogenous substances inhibiting the cell membrane sodium pump. A number of radioimmunoassays have been developed in order to study the clinical significance of ouabain. The results have been controversial with regard to the presence and chemical nature of plasma ouabainlike immunoreactivity. We have now measured ouabain in healthy and pregnant individuals using solid-phase extraction of plasma sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 38 publications
(50 reference statements)
1
25
0
1
Order By: Relevance
“…In agreement with previous studies, 15,21 we found higher levels of circulating ouabain in pregnant women ( Figure 10A). However, no significant differences in the steroid concentration were found at the different times tested.…”
Section: Abundance Of Circulating Ouabain In Human Fetal and Maternalsupporting
confidence: 93%
“…In agreement with previous studies, 15,21 we found higher levels of circulating ouabain in pregnant women ( Figure 10A). However, no significant differences in the steroid concentration were found at the different times tested.…”
Section: Abundance Of Circulating Ouabain In Human Fetal and Maternalsupporting
confidence: 93%
“…29 In our study, the average level of plasma EO was 14.7±5.7 pmol l -1 , nevertheless our patients were treated with RAAS blockers and/or b-blockers. In our study, the levels of EO were lower than in some studies in literature using other immunoassay methods (enzyme-linked immunosorbent assay, EIA), which are, however, not comparable with our results because of the use of different antibody and methods.…”
Section: Discussionmentioning
confidence: 56%
“…There now is strong evidence indicating that ouabain is a mammalian hormone that, like other steroid hormones, is synthesized and released from the adrenal gland (16,17,41). Circulating levels of ouabain in mammals is estimated to be in the picomolar range and has been reported to be significantly increased in conditions in which extensive cell growth and differentiation are required, including pregnancy (42), early postnatal life (43), and after unilateral nephrectomy (44), a condition that is associated with compensatory growth of the remaining kidney.…”
Section: Discussionmentioning
confidence: 99%